Hexokinase II in breast carcinoma: A potent prognostic factor associated with hypoxia‐inducible factor‐1α and Ki‐67. Issue 10 (21st August 2013) - Sato‐Tadano, Akiko; Suzuki, Takashi; Amari, Masakazu; Takagi, Kiyoshi; Miki, Yasuhiro; Tamaki, Kentaro; Watanabe, Mika; Ishida, Takanori; Sasano, Hironobu; Ohuchi, Noriaki
Abstract : Hypoxia‐inducible factor‐1α (HIF‐1α) mediates adaptive responses to changes under tissue hypoxia in carcinoma cells by controlling the expression of various target genes. Previous studies have demonstrated that HIF‐1α is associated with adverse clinical outcome in breast carcinoma patients, but details of HIF‐1α's role have remained largely unknown. Therefore, in this study, we examined the expression profiles of HIF‐1α‐induced genes in 10 breast carcinoma cases using microarray data. As a result, we demonstrated that the status of hexokinase II (HKII) was associated with carcinoma recurrence in patients with these genes. The enzyme HKII is involved in the first, and rate‐limiting, step of glycolysis, but its clinical significance has not yet been examined in breast carcinoma. Therefore, we immunolocalized HKII in 118 breast carcinomas, and HKII immunoreactivity was detected in 44% of the cases. It is significantly associated with histological grade, Ki‐67 labeling index and HIF‐1α immunoreactivity. Also, HKII status is significantly associated with increased risk of recurrence and adverse clinical outcome in breast cancer patients. Subsequent multivariate analysis demonstrated that HKII status was an independent prognostic factor for disease‐free survival of patients. These results all suggest that HKII is induced by HIF‐1α and plays important roles in the proliferation and/or progression of breast carcinoma possibly through increased glycolytic activity. The status of HKII is therefore considered a potent prognostic factor in human breast cancer patients.